Dynamic driving in seaports: Current and future applications - Julian Neugebauer; Leonard Heilig; Stefan Voß (Cleaner Logistics and Supply Chain)
While striving for sustainable operations, carriers, shipping companies, freight forwarders, and container terminal operators aim to ensure efficiency and competitive operations. Slow steaming, particularly for ocean-going cargo vessels, is a popular method to save fuel, leading to more cost-effective operations and reduced emissions. We analyze the application domains of slow steaming, floating car data (FCD) as well as dynamic driving and the methods enabling it. Notably, the paper identifies dynamic driving for straddle carriers (SCs) as a research gap and discusses its application. We present a feasibility study and insights from a project that develops a digital twin for the EUROGATE Container Terminal Hamburg (CTH), Germany. Data from the project is used to specifically examining the application of dynamic driving for SCs. The results show an estimated reduction in fuel consumption of up to 21%. Furthermore, we estimate 3% lower emissions for the container terminal.